Discourse patterns in primary mathematics classes - Bacungan, Amelia Ordona 1948- (1986)
This study described and analyzed the patterns and discourse in primary Mathematics classes using a tri-partite dimensional model which consists of Sinclair and Coulthard's linguistic analysis, Krashen's comprehensibility strategies and Henderson's concept venture moves.
Thesis (Ph.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Mathematics -- Study and teaching (Primary).; English languge -- Discourse analysis